A graphical approach to optimal source-sink matching in carbon capture and storage systems with reservoir capacity and injection rate constraints - Tan, Raymond Girard R. (Animo Repository, 2012)
Carbon capture and storage (CCS) is regarded as an important interim technology for the reduction of carbon dioxide (CO 2 ) emissions from large industrial facilities such as power plants and refineries. CCS involves capture of concentrated CO 2 streams from industrial flue gases, followed by subsequent secure storage in an appropriate natural reservoir. Such reservoirs include various geological formations such as depleted oil or gas wells, inaccessible coal seams and saline aquifers. In practice, such storage sites will have limitations on both CO 2 storage capacity and injection rate, subject to geological characteristics. In this work, a graphical methodology is proposed for optimally matching multiple CO 2 sources and storage sites or sinks within a predefined geographical region. The technique is developed based on analogies with existing graphical pinch analysis approaches for the synthesis of industrial resource conservation networks. A hypothetical case study is shown to illustrate the methodology. In addition, generalized principles for optimal CO 2 source-sink matching based on pinch analysis insights are discussed. © 2012 Elsevier B.V.